An evaluation of the effect of different solutions on the microhardness of aesthetic restoration (Mustansiria Dental Journal, 2018)
Dietary awareness is an important issue in modern society. The consumption ofcarbonated drinks is popular with the youth of today and the habit is carried over intoadulthood. One of the most important properties that determine the durability ofdental materials in the oral cavity is their resistance to dissolution or disintegrationand the longevity of dental restorations depends on the durability of the material andits properties, such as wear resistance, durability of the interface between tooth andrestoration and the level of tooth destruction.The aim of this study was to measure surface hardness of composite after storagein dry condition and after immersion in saliva and solutions that represent the populardiet.Fifty disk shaped specimens (5×2mm) were prepared from Z100 universalcomposite using polytetraflouroethylen mold. The specimens were divided into 5groups (n=10) and stored for 7 days at 37 Cْ in different types of storage conditions(dry condition, artificial saliva, coca cola, heptane and citric acid). After storage,Brinell Hardness Numbers were calculated. The data were analyzed with one – wayanalysis of variance (ANOVA) and LSD test.There was a highly significant difference when comparing the storage agents.Coca cola and citric acid solutions produced the highest reduction in microhardness ofcomposite. It was followed by heptanes, artificial saliva. The storage of specimens indry container produced the highest Brinell Hardness Numbers.Microhardness of composites stored in dry condition was the highest value,followed by artificial saliva, heptane solution, cola soft drink and citric acid . Acidsolutions have the potential to erode composite resin material and this reduction washighly significant, which means that people who consume acidic foods and drinksexcessively should be aware of their esthetic restorations.